A Review of Online Dyslexia Learning Modules - Anderson, Alida; Sarlo, Gabrielle L.; Pearlstein, Hannah; McGrath, Lauren M. (Frontiers in Education, 2020)
This paper presents a comprehensive review of publicly available online dyslexia learning modules with a particular focus on the extent to which modules address the prevalent myth that dyslexia is caused by “backwards reading.” The authors conducted a systematic internet search to identify publicly available online dyslexia learning modules and coded the content across education, neurocognition, and policy disciplinary domains. We identified 18 topics across a small number (N=14) of publicly available modules that focused on dyslexia, with only two modules directly addressing this dyslexia myth. While both identified this myth as false, neither provided information about the neurocognitive underpinnings of dyslexia to explain why this myth is false. This review will be useful for guiding further development of online dyslexia learning modules which are urgently needed due to persisting misinformation about this disorder. The coded content reviews of each module will also be beneficial for directing attention to existing resources for professional development on dyslexia.